2020
DOI: 10.3389/fcell.2020.574940
|View full text |Cite
|
Sign up to set email alerts
|

EZH2-Inhibited MicroRNA-454-3p Promotes M2 Macrophage Polarization in Glioma

Abstract: Glioma is a primary intracranial tumor with high incidence and mortality. The oncogenic role of EZH2 has been reported in glioma. EZH2 inhibited microRNA-454-3p (miR-454-3p) by binding to its promoter in chondrosarcoma cells. Therefore, our study aimed to identify whether EZH2 regulated M2 macrophage polarization in glioma via miR-454-3p. Clinical samples of different grades of glioma and glioma cells were collected and immunohistochemistry and RT-qPCR demonstrated that EZH2 was highly expressed in glioma tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…There is a fact that up to 30–50% of the immune cells in glioma are tumor-associated macrophages (TAMs). 38 Previous investigators have classified TAMs into M1-type macrophages, a proinflammatory phenotype associated with a favorable survival outcome, and M2-type macrophages, an immunosuppressive phenotype associated with a poor survival outcome. 39 Our results suggested that M2-type macrophages had an overwhelming advantage in numbers compared with other immune cells, and the PRGPI-high group with poor survival outcome had significantly higher enrichment of M2-type macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…There is a fact that up to 30–50% of the immune cells in glioma are tumor-associated macrophages (TAMs). 38 Previous investigators have classified TAMs into M1-type macrophages, a proinflammatory phenotype associated with a favorable survival outcome, and M2-type macrophages, an immunosuppressive phenotype associated with a poor survival outcome. 39 Our results suggested that M2-type macrophages had an overwhelming advantage in numbers compared with other immune cells, and the PRGPI-high group with poor survival outcome had significantly higher enrichment of M2-type macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the histone methyltransferase EZH2 utilizes a methylation modification to inhibit miR-454-3p and promotes the m6A modification of PTEN to polarize macrophages toward the M2 phenotype. Of note, combined treatment with EZH2 inhibitors and PD-1 inhibitors restored the cytotoxicity of macrophages and blocked the progression of CSCs [ 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 ].…”
Section: Therapeutic Strategies Targeting Cscs and Tamsmentioning
confidence: 99%
“…For example, in hepatocellular carcinoma, miR-144/miR-451a is silenced by EZH2 and promotes M1 polarization, enhancing anti-tumor immunity [ 221 ]. In addition, EZH2 is inhibited in gliomas, mediated in a PRC2-dependent manner through miRNA-454-3p, immunosuppression or M2-like macrophage polarization [ 222 ]. However, macrophage infiltration is involved in the regulation of the LOX family protein (LOXL4) by EZH2-miR-29b/miR-30d in invasive breast cancer, and contributes to extracellular matrix remodeling [ 223 ].…”
Section: Immune Regulation By Ezh2 In Tmementioning
confidence: 99%